2001
DOI: 10.1021/bc010027n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Studies of 5-Aminolevulinic Acid-Containing Dendrimers for Photodynamic Therapy

Abstract: Using a convergent growth approach, a series of novel 5-aminolevulinic acid (ALA)-containing dendrimers have been synthesized. In these molecules, ALA residues are attached to the periphery by ester linkages, with amide bonds connecting the dendrons. Three first-generation dendrimers, bearing either 6 or 9 ALA residues, were synthesized by attachment of a tris(Boc-protected ALA)-containing wedge (1) to a di- or tripodent aromatic, or tripodent aliphatic core. Two second generation 18-ALA-containing dendrimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 23 publications
0
73
0
1
Order By: Relevance
“…5-ALA was purchased from Sigma-Aldrich (Poole, United Kingdom). The synthesis of the dendrimer was carried out as published previously (20). 5-(N-ethyl-Nisopropyl)amirolide (EIPA) and N-ethylmaleimide (NEM) were purchased from Fisher Scientific (Loughborough, United Kingdom; ACROS).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-ALA was purchased from Sigma-Aldrich (Poole, United Kingdom). The synthesis of the dendrimer was carried out as published previously (20). 5-(N-ethyl-Nisopropyl)amirolide (EIPA) and N-ethylmaleimide (NEM) were purchased from Fisher Scientific (Loughborough, United Kingdom; ACROS).…”
Section: Chemicalsmentioning
confidence: 99%
“…In principle, a dendrimeric nanovehicle bearing a high ALA 'payload' can per molecule deliver a much higher quantity of ALA to cells. A preliminary investigation of dendritic ALA derivatives showed that they were capable of delivering ALA to cells for conversion into PpIX (20). The ALA residues were attached via ester linkages, which were then cleaved enzymatically within the cells to liberate the ALA. Several smaller dendritic ALA prodrugs have also been investigated recently to compare the effect of changes in the molecular structure (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, several chemical approaches have been attempted to improve the incorporation of ALA and also its selectivity. One approach has been to use more lipophilic ALA derivatives, such as alkyl or ethyleneglycol esters, which are potential substrates for cellular esterases (Kloek and Beijersbergen, 1996;Gaullier et al, 1997;Berger et al, 2000;Uehlinger et al, 2000), or different delivery systems including dendrimers (Battah et al, 2001Di Venosa et al, 2006), or liposomes (Casas et al, 2002;Casas and Batlle, 2006). 5-Aminolaevulinic acid prodrug ester derivatives have been widely studied (Kloek and Beijersbergen, 1996;Peng et al, 1996;Gaullier et al, 1997;Kloek et al, 1998;Casas et al, 1999;Eleouet et al, 2000;Brunner et al, 2003;Lopez et al, 2004), in particular the methyl and hexyl ester derivatives, and approval has been granted for the treatment of actinic keratosis and basal cell carcinoma using the methyl ester derivative in Europe and Australia.…”
mentioning
confidence: 99%
“…In the latter case, various iron chelators (25)(26)(27)(28) and chemotherapeutic agents (29) have been shown to be effective in enhancing levels of PpIX production upon administration of ALA. The use of ALA conjugated to first-or second-generation dendrimers also results in enhanced porphyrin synthesis with such prodrugs at low concentrations compared with an equivalent dose of ALA itself (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%